Fabrication And Characterizations Of Porous Zinc Oxide Thin Films - Ching, Chin Guan (2013)
he main objectives of this project are to study the fabrication of porous ZnO thin films by using ultraviolet light assisted electrochemical etching method and to characterize the surface morphologies, the cross sectional structure and the optical properties of the porous samples. In addition, the determination of porosities and thicknesses of selected porous ZnO thin films with the use of infrared (IR) reflectance spectra and effective medium theories is also demonstrated. In this work, three fabrication experiments of porous ZnO are carried out. In these experiments, the effects of etchant concentration, etching potential and etching time on the fabricated porous ZnO thin films are investigated separately. The fabricated porous ZnO thin films are characterized by using scanning electron microscopy (SEM), photoluminescence (PL) spectroscopy and Fourier transform infrared spectroscopy. SEM results revealed that hillock like porous ZnO thin films are successfully obtained throughout this study. The cross sectional SEM images also indicated the occurrence of anisotropic dominated etching during the electrochemical etching of ZnO thin films. Besides that, the PL characterization results showed that there is enhancement of near band edge emission peak in most of the porous samples. IR reflectance results revealed that an additional resonance hump in the reststrahlen region induced by the hillock like porous structure. Through the fitting of the IR reflectance spectra, good agreement between the theoretical and experimental spectra is obtained.